Impaired left atrial function predicts inappropriate shocks in primary prevention implantable cardioverter‐defibrillator candidates. (22nd June 2017) - Tao, Susumu; Ashikaga, Hiroshi; Ciuffo, Luisa A.; Yoneyama, Kihei; Lima, Joao A.C.; Frank, Terry F.; Weiss, Robert G.; Tomaselli, Gordon F.; Wu, Katherine C.
Abstract: Introduction: Inappropriate implantable cardioverter‐defibrillator (ICD) shocks, commonly caused by atrial fibrillation (AF), are associated with an increased mortality. Because impaired left atrial (LA) function predicts development of AF, we hypothesized that impaired LA function predicts inappropriate shocks beyond a history of AF. Methods and results: We prospectively analyzed the association between LA function and incident inappropriate shocks in primary prevention ICD candidates. In the Prospective Observational Study of ICD (PROSE‐ICD), we assessed LA function using tissue‐tracking cardiac magnetic resonance (CMR) prior to ICD implantation. A total of 162 patients (113 males, age 56 ± 15 years) were included. During the mean follow‐up of 4.0 ± 2.9 years, 26 patients (16%) experienced inappropriate shocks due to AF (n = 19; 73%), supraventricular tachycardia (n = 5; 19%), and abnormal sensing (n = 2; 8%). In univariable analyses, inappropriate shocks were associated with AF history prior to ICD implantation, age below 70 years, QRS duration less than 120 milliseconds, larger LA minimum volume, lower LA stroke volume, lower LA emptying fraction, impaired LA maximum and preatrial contraction strains (Smax and SpreA ), and impaired LA strain rate during left ventricular systole and atrial contraction (SRs and SRa ). In multivariable analysis, impaired Smax (hazard ratio [HR]: 0.96, P = 0.044), SpreA (HR: 0.94, P = 0.030), and SRa (HR: 0.25, P < 0.001) were independently associated with inappropriate shocks. The receiver‐operating characteristics curve showed that SRa improved the predictive value beyond the patient demographics including AF history (P = 0.033). Conclusion: Impaired LA function assessed by tissue‐tracking CMR is an independent predictor of inappropriate shocks in primary prevention ICD candidates beyond AF history.